TRANSFORMATIVE ADAPTIVE LEADERSHIP IN THE DIGITAL AGE: A SYSTEMATIC REVIEW OF EMERGING PARADIGMS AND SOCIO-ECONOMIC IMPLICATIONS FOR ORGANIZATIONAL RESILIENCE - Sundowo, Asep Winardi; Hermawan, Anton; Wijayanto, Dedi; Ikhsan, M.; Rachmad, Faizal; Kuswoyo, Yoyo; S., Sherly Anggraini (Ikatan Dosen Menulis, 2024)
This paper explores the evolving nature of leadership amidst rapid technological advancements and socio-economic shifts. It highlights the limitations of traditional leadership models in addressing complex challenges posed by digital transformation and global disruptions. The study synthesizes research on the intersection of transformational and adaptive leadership, emphasizing the need for an integrated approach. Findings suggest that leaders who combine transformational vision with adaptive strategies can better navigate technological changes, foster innovation, and enhance organizational resilience. This systematic review also outlines significant challenges, such as balancing technological integration and human factors, and offers insights into effective leadership practices in the digital era.